Pengaruh Kompensasi terhadap Kinerja Karyawan Melalui Komitmen Organisasi Sebagai Variabel Intervening Pada PT. Duren Mandiri Fortuna Jambi - Roki, Roki; Sumarni, Sumarni; Ratnawati, Rts. (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The purpose of writing this thesis is to examine the influence of compensation variables on employee performance and organizational commitment as intervening variables at PT. Duren Mandiri Fortuna Jambi. Data collection was carried out by distributing questionnaires with a Likert scale to 72 employees of PT. Duren Mandiri Fortuna Jambi. Data testing techniques used include validity and reliability tests, R-Square testing and hypothesis testing by bootstrapping using Smart PLS 3. The results show that compensation has a positive and significant effect on employee performance at PT.Duren Mandiri Fortuna Jambi, compensation has an effect positive and significant to organizational commitment at PT. Duren Mandiri Fortuna Jambi, organizational commitment has a positive and significant effect on employee performance at PT.Duren Mandiri Fortuna Jambi, compensation through organizational commitment has a positive and significant effect on employee performance. Therefore, it is recommended that companies from the compensation aspect need to pay attention to the compensation , from the aspect of organizational commitment is one of the factors that affect employee performance, from the aspect of employee performance it needs to be improved.